2015
DOI: 10.7717/peerj.864
|View full text |Cite
|
Sign up to set email alerts
|

Properties evaluation of silorane, low-shrinkage, non-flowable and flowable resin-based composites in dentistry

Abstract: Purpose. This study tested the null hypothesis that different classes of direct restorative dental materials: silorane-based resin, low-shrinkage and conventional (non-flowable and flowable) resin-based composite (RBC) do not differ from each other with regard to polymerization shrinkage, depth of cure or microhardness.Methods. 140 RBC samples were fabricated and tested by one calibrated operator. Polymerization shrinkage was measured using a gas pycnometer both before and immediately after curing with 36 J/cm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…For instance, compared to the Z350 flowable composite with a filler content of 65 wt%, Z250 conventional composite (both Filtek™ Supreme, 3M ESPE, USA) with a filler content of 82 wt% showed a significantly lower shrinkage strain of 0.70% [ 37 ]. The low shrinkage flowable composite performed similarly to non-flowable composite with a significant difference compared to the other flowable resin-based composites, according to Maia et al [ 16 ].…”
Section: Development Of Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…For instance, compared to the Z350 flowable composite with a filler content of 65 wt%, Z250 conventional composite (both Filtek™ Supreme, 3M ESPE, USA) with a filler content of 82 wt% showed a significantly lower shrinkage strain of 0.70% [ 37 ]. The low shrinkage flowable composite performed similarly to non-flowable composite with a significant difference compared to the other flowable resin-based composites, according to Maia et al [ 16 ].…”
Section: Development Of Discussionmentioning
confidence: 91%
“…Maia et al, in their study concluded that the flowable silorane-based resin exhibited the least polymerization shrinkage among other flowable polymeric composites. Although siloranes are not often on the market in terms of matrix, a low shrinkage flowable composite performed similarly to a non-flowable one [ 16 ]. Among various novel monomers found in commercial products, glycero-phosphate dimethacrylate (GPDM) is also common.…”
Section: Development Of Discussionmentioning
confidence: 99%
“…They found that Filtek Z250 and Filtek P60 composites showed the least and highest percentage of shrinkage among the tested materials, respectively. In a study conducted by Maia et al .,[ 24 ] the polymerization shrinkage was evaluated by gas pycnometer method. They found that the Silorane-based composites presented the lowest value for shrinkage, followed by the nonflowable resin-based composites (RBCs).…”
Section: Measurement Of Shrinkage-strainmentioning
confidence: 99%
“…Polymers 2021, 13, x FOR PEER REVIEW 3 of 19 people have been working to optimize their performances, but they still have some defects that cannot be ignored such as polymerization shrinkage and defective physical and mechanical properties [8]. Resin-based composites have undergone many modifications as they evolved and represent the most relevant restorative materials in dental practice today [9]. In this review, the rheological and mechanical properties of resin-based restorative materials with different indications (e.g., dental filling composite, dental adhesive and resin luting cement) are discussed, and the cutting-edge techniques, challenges and future development of resin-based dental restorative materials are also covered.…”
Section: Introductionmentioning
confidence: 99%